Host defence against Staphylococcus aureus biofilms by polymorphonuclear neutrophils: oxygen radical production but not phagocytosis depends on opsonisation with immunoglobulin G - Stroh, Petra; Günther, Frank; Meyle, Eva; Prior, Birgit; Wagner, Christof; Hänsch, Gertrud Maria (Immunobiology, 2011)
Bacterial biofilms are increasingly recognised as a major cause of persistent infection and destructive inflammatory processes. In patients with biofilm infection, massive infiltration of leukocytes, particularly polymorphonuclear neutrophils is seen, and previous in vitro studies showed that PMN were able to phagocytose Staphylococcus aureus biofilms. We now addressed the question whether opsonisation of biofilms with immunoglobulin G and complement enhances the efficiency of phagocytosis, as it has been shown for "free-living" planktonic bacteria and other particulate materials. We found that incubation of biofilms with normal human serum resulted in IgG binding and in complement activation with deposits on the biofilm of C3bi. This "opsonisation", however, did not affect the adherence of PMN to the biofilms nor did it enhance degranulation or phagocytosis. The clearance of biofilms, however, was increased, and the oxygen radical production by the PMN depended critically on the coating of biofilms with IgG.